Al-Ribhu (Keuntungan) Dan Ketentuannya Dalam Fiqh Islam - Yusnaidi (Prodi Hukum Keluarga Fakultas Syariah dan Hukum UIN Ar-Raniry, 2022)
Al-Ribhu (profit) is a goal that every business actor wants to achieve in carrying out economic activities. In Islam, it does not regulate certain limits on a profit that must be achieved by business actors in carrying out economic activities. Basically every economic activity in Islam is based on Islamic law, so that every economic activity carried out by every business actor cannot be separated from a halal and good process in obtaining profits. In this study, we will discuss Al-Ribhu, analyze existing definitions based on verse arguments and hadith arguments, and put forward some opinions of scholars related to Al-Ribhu in economic activities. This study also discusses the Al-Ribhu law which is in accordance with the Shari'a and the Al-Ribhu law which is not in accordance with the Shari'a in the implementation of economic activities. This study uses a normative analytical research methodology with the type of research that is library research. In Islamic law it allows every business actor to profit from every economic transaction, which of course is obtained in a lawful way, and Islamic law forbids all profits (profits) obtained through fraudulent methods and market exploitation. Shari'a does not limit profits (profits) to a certain amount but is released to market conditions, provided that market conditions are normal and there is no exploitation.